2022
DOI: 10.1126/scirobotics.abn4155
|View full text |Cite
|
Sign up to set email alerts
|

3D-printed biomimetic artificial muscles using soft actuators that contract and elongate

Abstract: Biomimetic machines able to integrate with natural and social environments will find ubiquitous applications, from biodiversity conservation to elderly daily care. Although artificial actuators have reached the contraction performances of muscles, the versatility and grace of the movements realized by the complex arrangements of muscles remain largely unmatched. Here, we present a class of pneumatic artificial muscles, named GeometRy-based Actuators that Contract and Elongate (GRACE). The GRACEs consist of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…[80][81][82] Soft actuators are widely used in the area of artificial muscles, robotics, and haptic systems. [83][84][85] By combining functional materials and transfer printing technology, various soft functions can be achieved, such as mechanical bending, 86,87 drug delivery, 88,89 and temperature management. 90,91 Xinge Yu et al reported a skin-integrated haptic interface system for virtual and augmented reality (Fig.…”
Section: Transfer Printing For Bioelectronicsmentioning
confidence: 99%
“…[80][81][82] Soft actuators are widely used in the area of artificial muscles, robotics, and haptic systems. [83][84][85] By combining functional materials and transfer printing technology, various soft functions can be achieved, such as mechanical bending, 86,87 drug delivery, 88,89 and temperature management. 90,91 Xinge Yu et al reported a skin-integrated haptic interface system for virtual and augmented reality (Fig.…”
Section: Transfer Printing For Bioelectronicsmentioning
confidence: 99%
“…The emulation of this process becomes a promising technology in bioinspired electronics for intelligent robotics. For example, to produce the bionic electric skin, there are numerous skilled designs in both structure and materials for accurate and efficient stimuli sensing. Meanwhile, various artificial muscles based on asymmetric expansion, , pneumatic inflation, and hydraulic actuation , with specific system programming were developed, for instance. Consequently, in terms of mimicking biological conditioned reflex, which receives external stimuli and produces informative synaptic-responsive and motor outputs, the complex and incompatible production processes of electric skins and artificial muscles lead to high production costs and delicate preparation of intelligent robotics. , Therefore, one of the key challenges in the field of commercial intelligent soft robotics construction is developing a kind of novel multifunctional intelligent material for an efficient manufacturing process.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16,41 ] Therefore, achieving high‐speed and low‐energy actuation of m‐SPAs remains an open challenge (Table S1 and Figure S1a, Supporting Information). [ 13,14,18,22,34,42–47 ]…”
Section: Introductionmentioning
confidence: 99%